OCORRÊNCIA E FLUTUAÇÃO POPULACIONAL DE ÁCAROS EM MAMOEIROS CULTIVADOS EM AQUIDAUANA, MS - SILVA, Leonardo Gomes Duran; CELOTO, Mercia Ikarugi Bomfim; VOLPATO, Túlio; ROCKENBACH, Roanita Iara; PERES, Nathália Dias; SILVA, Adriana de Castro Correia (ANAIS DO ENIC, 2020)
-